Disentangling the performance effects of efficiency and bargaining power in horizontal growth strategies: An empirical investigation in the global retail industry - Moatti, Valérie; Ren, Charlotte R.; Anand, Jaideep; Dussauge, Pierre (Strategic Management Journal, 2015)
Mergers and acquisitions ( M&A) and organic growth are two common strategies to achieve horizontal growth. In this study, we disentangle two distinct sources of firm performance corresponding to different theoretical perspectives on firm size: firms' bargaining power with respect to suppliers and customers, and operating efficiency arising from scale economies. We conceptually argue and empirically show that relatively, M&A enhance bargaining power in the short term while organic growth enhances operating efficiency over the long term. In order to disaggregate these effects, we use accounting rather than financial or managerial data and test our predictions in the global retail industry over a 20‐year period. We examine implications of these results for sustainability of size‐based competitive advantages . Copyright © 2014 John Wiley & Sons, Ltd.